Aerotaxy: gas-phase epitaxy of quasi 1D nanostructures. (14th October 2020) - Sivakumar, Sudhakar; Persson, Axel R; Metaferia, Wondwosen; Heurlin, Magnus; Wallenberg, Reine; Samuelson, Lars; Deppert, Knut; Johansson, Jonas; Magnusson, Martin H
Abstract: Cost- and resource-efficient growth is necessary for many applications of semiconductor nanowires. We here present the design, operational details and theory behind Aerotaxy, a scalable alternative technology for producing quality crystalline nanowires at a remarkably high growth rate and throughput. Using size-controlled Au seed particles and organometallic precursors, Aerotaxy can produce nanowires with perfect crystallinity and controllable dimensions, and the method is suitable to meet industrial production requirements. In this report, we explain why Aerotaxy is an efficient method for fabricating semiconductor nanowires and explain the technical aspects of our custom-built Aerotaxy system. Investigations using SEM (scanning electron microscope), TEM (transmission electron microscope) and other characterization methods are used to support the claim that Aerotaxy is indeed a scalable method capable of producing nanowires with reproducible properties. We have investigated both binary and ternary III–V semiconductor material systems like GaAs and GaAsP. In addition, common aspects of Aerotaxy nanowires deduced from experimental observations are used to validate the Aerotaxy growth model, based on a computational flow dynamics (CFD) approach. We compare the experimental results with the model behaviour to better understand Aerotaxy growth.